2013
DOI: 10.1105/tpc.113.112359
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphorylated Pathway of Serine Biosynthesis Is Essential Both for Male Gametophyte and Embryo Development and for Root Growth in Arabidopsis

Abstract: This study characterizes the phosphorylated pathway of Ser biosynthesis (PPSB) in Arabidopsis thaliana by targeting phosphoserine phosphatase (PSP1), the last enzyme of the pathway. Lack of PSP1 activity delayed embryo development, leading to aborted embryos that could be classified as early curled cotyledons. The embryo-lethal phenotype of psp1 mutants could be complemented with PSP1 cDNA under the control of Pro35S (Pro35S:PSP1). However, this construct, which was poorly expressed in the anther tapetum, did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 58 publications
6
77
0
Order By: Relevance
“…Both PGDH and EDA9 were preferentially expressed in roots, which supports the idea that the PPSB plays an important role in supplying Ser to this organ or to other nonphotosynthetic tissues (Ho and Saito, 2001;Cascales-Miñana et al, 2013). It has also been suggested that the PPSB could be relevant in photosynthetic organs, especially in the dark when the pathway of carbon flux from glycolate to Ser ceases to function (Kleczkowski and Givan, 1988;Ho and Saito, 2001).…”
Section: Discussionsupporting
confidence: 69%
“…Both PGDH and EDA9 were preferentially expressed in roots, which supports the idea that the PPSB plays an important role in supplying Ser to this organ or to other nonphotosynthetic tissues (Ho and Saito, 2001;Cascales-Miñana et al, 2013). It has also been suggested that the PPSB could be relevant in photosynthetic organs, especially in the dark when the pathway of carbon flux from glycolate to Ser ceases to function (Kleczkowski and Givan, 1988;Ho and Saito, 2001).…”
Section: Discussionsupporting
confidence: 69%
“…the Phosphorylated Pathway of Serine Biosynthesis (PPSB) has been known since the 1950s, but has been studied relatively little, probably because it was considered of minor significance as compared with the Glycolate pathway. in the associated study 1 , we described for the first time in plants the in vivo functional characterization of the PPSB, by targeting the phosphoserine phosphatase (PSP1), the last enzyme of the pathway. Following a gain-and loss-of-function approach in Arabidopsis, we provided genetic and molecular evidence for the essential role of PSP1 for embryo and pollen development, and for proper root growth.…”
mentioning
confidence: 99%
“…It was hypothesized that the main function of GAPCps in roots is to supply 3-PGA to the phosphorylated pathway of serine biosynthesis (PPSB; Muñoz-Bertomeu et al, 2009). This hypothesis was later confirmed by the characterization of the PPSB (Cascales-Miñana et al, 2013). Double GAPCp1 and GAPCp2 mutants (gapcp1gapcp2) also display a drastic reduced growth of the aerial part (AP; Muñoz-Bertomeu et al, 2009), suggesting a role of the enzyme in this organ.…”
mentioning
confidence: 75%